SISTEM APLIKASI KOPERASI KARYAWAN PT SUMBER REZEKI BERBASIS WEB DENGAN METODE RAPID APPLICATION DEVELOPMENT - Serta Manullang; Asep Muhidin; Nisa Nurhidayanti (Sekolah Tinggi Manajemen Informatika dan Komputer Jayakarta, 2023)
In the era This study aims to develop a web-based employee cooperative application system with the rapid application development (RAD) method that can facilitate the employee cooperative management process, such as recording member data, managing deposits, borrowing money, installment payments, and financial statements. The RAD method is used because it allows for fast and efficient system development by involving users in every stage of development. This research was conducted with qualitative and quantitative approaches. Data was collected through interviews with cooperative administrators, employees and cooperative members who are users of the application system. In addition, data was also collected through observations of the employee cooperative system that has been running. The result of the study is a web-based employee cooperative application system that has been developed with the RAD method. This system has features that can help employee cooperatives manage financial activities more efficiently and effectively. With the web-based employee cooperative application system with the RAD method, it is expected to facilitate employee cooperatives so that they can improve the performance and growth of cooperatives. In addition, users of the RAD method in the development of this application system can also provide benefits in the development of application systems in the future.